SOCIAL CLIMBER IDENTITY AND MEMORY : POTRET DIRI SEBAGAI OBJEKTIVITAS HIPERREALITAS KEHIDUPAN DAN DEGRADASI MEMORI - Yudhistira, Nurfian (Universitas Widya Mataram, 2020)
This study examines the development of photographic technology that facilitates the development of the phenomenon of social climbing by highlighting the hyperreality of social media, thereby resulting in the emergence of a new identity for social climbers. Photography technology has evolved over time. Digital technology has created instant technology that makes it easy for camera users to operate cameras with automatic adjustment features, therefore the technology industry is constantly looking for ways to develop and make smartphones. Smartphones integrate image and communication technology into one device, making it easier for users to communicate. This smart phone supports online access to social media because of its features that can be connected to the internet. So anyone can share their photography using this tool and also social media. social media makes it easy for everyone to access information including personal activities that are shared, so that phenomena that are often referred to as social climbing phenomena are phenomena marked by social media users who are competing to improve their social status on online social media. The phenomenon of social climbing makes someone create a new identity for themselves on social media. Creating a life that is exaggerated from its original reality or also called hyperreality. This study aims to provide education related to the use of photography and social media, so that people do not fall into the phenomenon of false identities in social media.